2022
DOI: 10.3390/rs14164096
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Stratospheric Gravity Waves in the Asian Monsoon Region Derived from COSMIC-2 Data

Abstract: COSMIC-2 (Constellation Observing System for Meteorology, Ionosphere and Climate- 2) dry temperature profile data from December 2019 to November 2021 are used to study stratospheric gravity waves (GWs) in the Asian monsoon region. The stratosphere between 20 and 50 km is divided into the lower, middle, and high layers based on the vertical distribution of the mean potential energy (Ep) and the horizontal distribution of GW Ep in these three layers, and their seasonal changes are analyzed. The source and propag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 38 publications
3
9
0
Order By: Relevance
“…The data were downloaded from https://cdaac-www.cosmic.ucar.edu/ (accessed on 1 August 2022). The Asian monsoon is selected as the study area, with the specific domain being 70-150 • E and 15-45 • N. Qu et al [18] reported the monthly average sampling density of COSMIC-2 data to be 25 times at 15-30 • N and 15 times at 30-45 • N, with a 2.5 • × 2.5 • grid resolution during this period. The vertical range of the COSMIC-2 dry temperature profile data is 0-60 km.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The data were downloaded from https://cdaac-www.cosmic.ucar.edu/ (accessed on 1 August 2022). The Asian monsoon is selected as the study area, with the specific domain being 70-150 • E and 15-45 • N. Qu et al [18] reported the monthly average sampling density of COSMIC-2 data to be 25 times at 15-30 • N and 15 times at 30-45 • N, with a 2.5 • × 2.5 • grid resolution during this period. The vertical range of the COSMIC-2 dry temperature profile data is 0-60 km.…”
Section: Methodsmentioning
confidence: 99%
“…For the COSMIC-2 temperature profiles, the individual temperature profiles (T) consist mainly of background (T) and perturbation (T ) components (i.e., T = T + T) [16]. Due to the irregular vertical resolution of the raw observational data, each raw dry temperature profile was interpolated to a regular 100 m resolution [18]. All temperature profiles were then processed horizontally and vertically.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations